MENINGKATKAN KUALITAS ORGANISASI DENGAN MANAJEMEN EXCELLENCE: SUATU TINJAUAN PUSTAKA - Rokhayati, Isnaeni (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2015)
The development of management science today requires effective management and efficient management to improve the quality of the organization with management excellence. So the ability and skills of managers and strategies are needed to realize the goals of the organization that has been set. Achievement of quality management organization with excellence necessary steps and strategy of the tapat supported by the management of the external environment are controlled, the existence of innovative change management and acceptable, and management of organizational culture conducive. Implement management excellence is not separated from the management functions of planning, organizing, directing, and monitoring saffing always implemented appropriately in the management of the organization as well as the role and ability of the manager must be improved in order to achieve the goal of improving the quality of the organization. Keywords; quality of the organization, management excellence, functions of management, change management, and organizational culture.